The sales effect of "Free App of the Day" on Amazon Appstore: An empirical study - Hong Chen; Kevin Lachaud; Wenqi Zhou (Digital Business, 2022)
This study aims to understand the impact of the "Free App of the Day" (FAD) promotion on app sales during the post-promotion period on Amazon Appstore. The FAD promotion spotlights a single paid app by presenting it on the frontpage of Appstore, offers the app free of charge for one day, and broadcasts the promotion through Amazon's social media channels. This digital marketing strategy differs from the commonly adopted digital free sampling and sponsorship practices. In this study, we empirically examine its potential negative effect by analyzing a panel data set of FAD app sales and reviews. We find evidence that, when the app promotion expires, the price rebounding to the pre-promotion level discourages online customers from purchasing the app. We also observe an elevated amount of promotion-induced reviews generated at a high velocity during early days of the post-promotion. We conclude that these promotion-induced reviews are less influential than organic reviews.
Keywords: 650; Free app of the day; Digital free sampling; eWOM; Price rebound; Promotion-induced user reviews